Heavy Metal Removal Using Nanoparticles: A Review - Abhishek; Singh , Manvender; Dhull , Vikas (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Increased industrial activities and their improper handling of the by-products leads to contamination of the environment and the injudicious usage have led to air, soil and water/aquatic pollution. The main causative agent now-a-days are the heavy metal ions and thus there is a greater need to treat environmental toxicity. There are several methods for treating are developed such as chemical precipitation, filtration, and adsorption but they have some drawbacks such as too expensive with low efficiency in removing the heavy metals and along with toxicity. So, for to deal with such aspect the emerging nanotechnology have gained popularity. Several nanoparticles are being synthesized to remove the heavy metals metal ion inside the water. Heavy metal toxicity is being dealt by the help of nanoparticles and nanomaterials. In this review, some nanomaterials are produced such as silver nanoparticles, gold nanoparticles and metal oxide nanomaterials have been described that efficiently remove the heavy metals present in the water. This review aims at remediation of heavy metal toxicity in the water with help of nanomaterials in the most efficient and effective manner.